EFEKTIVITAS KEBIJAKAN BANTUAN LANGSUNG TUNAI DANA DESA (BLT-DD) KEPADA MASYARAKAT YANG TERKENA DAMPAK COVID-19 DI DESA SEMELINANG DARAT KECAMATAN PERANAP - Syaprianto; Herman (Jurnal PubBis, 2023)
One of the impacts of Covid-19 is the decline in the community's economy and to overcome the impact of Covid-19, the government made a policy, namely by providing assistance to the community, known as Village Fund Direct Cash Assistance (BLT-DD). In distributing the Village Fund BLT, the village government was considered not to be on time and the village government was considered to be less thorough because there were still people who received the Village Fund BLT who received other social assistance. Even though, according to the provisions, recipients of social assistance may not receive Village Fund BLT assistance. This study aims to find out how the Village Fund Direct Cash Assistance (BLT-DD) is distributed to the poor affected by Covid 19. This research uses a qualitative method and the theory that researchers use in this study is the theory of effectiveness according to Nugroho. Based on the results of the study, the Semelinang Darat village government in distributing Village Fund Direct Cash Assistance (BLT-DD) to communities affected by Covid-19 has been implemented, but there are still people who receive other social assistance who receive BLT Village Funds. So the suggestion in this study is that data on recipients of social assistance needs to be re-datad, so that no community that receives direct village cash assistance (BLT-DD) also receives social assistance from the government. Keywords: Evaluation, Village Fund BLT